Peranan Visum Et Repertum Sebagai Alat Bukti Terhadap Tindak Pidana Penganiayaan Berat - Azis, Iis Wulandari; Hamsir, (Alauddin Law Development Journal, 2022)
This study aims to determine the strength of the proof of visum et repertum in determining the direction of the indictment by the public prosecutor against the case of severe persecution in Decision No. The approach used in this research is the statutory and case approach. The type of research used is qualitative. The data sources include primary data, in the form of interviews and observations and secondary data in the form of journals, books and data on the internet related to research. The results of this study indicate that Visum et repertum is authentic evidence made in a predetermined form (letter) and made by a doctor as an authorized official. In making the indictment in the Decision No.97/Pid.B/2019/PN Makassar case visum et repertum also has a fairly large role in helping the Public Prosecutor to prove the truth of the elements of the Article deemed to have been violated by the defendant. Then, the position of visum et repertum in cases of criminal acts of persecution is as evidence of a letter as regulated in Article 143 of the Criminal Procedure Code. Although it is not absolutely necessary to have a visum et repertum in proving a criminal case, but to strengthen the judge's conviction, it is better if the visum et repertum must still exist, especially criminal acts whose object is the human body.